Distribution of endotoxin in maternal and fetal body with intrahepatic cholestasis of pregnancy and its association with adverse fetal outcome - Xiaomei Huang; Lei Lei; Fan Feng; Yong Shao (BMC, 2022)
Abstract Background Intrahepatic cholestasis of pregnancy is a pregnancy-specific liver disease. In this study, we sought to explore the distribution of lipopolysaccharide in the maternal body, and its effect on the fetal body in the intrahepatic cholestasis of pregnancy mice. It provides a new sight for the clinical treatment of women with intrahepatic cholestasis of pregnancy. Methods The serum levels of lipopolysaccharide and lipopolysaccharide binding protein in women with intrahepatic cholestasis of pregnancy were analyzed. To assess the association between lipopolysaccharide levels and adverse fetal outcomes, ursodeoxycholic acid, resveratrol, and phosphatidylinositol-3-kinase inhibitor were employed in intrahepatic cholestasis of pregnancy mice, and we studied the fluorescence intensity and distribution of lipopolysaccharide in mice with intrahepatic cholestasis of pregnancy. Results Our data indicated significantly elevated levels of lipopolysaccharide and lipopolysaccharide binding protein in women with intrahepatic cholestasis of pregnancy. In vivo fluorescence imaging revealed that the intensity of lipopolysaccharide in mice with intrahepatic cholestasis of pregnancy was higher than that in the control group, and decreased after ursodeoxycholic and resveratrol treatment. The fluorescence intensity analysis indicated that lipopolysaccharide levels in maternal liver, placenta, fetal brain and fetal liver were significantly higher in the intrahepatic cholestasis pregnancy mice group than in the control group. Conclusions This study provided evidence of endotoxin distribution in maternal liver, placenta, fetal liver and fetal brain in mice with intrahepatic cholestasis of pregnancy. Ursodeoxycholic acid and resveratrol treatment effectively reduced lipopolysaccharide levels in pregnant mice with intrahepatic cholestasis of pregnancy.